2017
DOI: 10.5487/tr.2017.33.1.055
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Melanogenic Effect ofOenothera laciniataMethanol Extract in Melan-a Cells

Abstract: We evaluated the antioxidant activity and anti-melanogenic effects of Oenothera laciniata methanol extract (OLME) in vitro by using melan-a cells. The total polyphenol and flavonoid content of OLME was 66.3 and 19.0 mg/g, respectively. The electron-donating ability, 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical-scavenging activity, and superoxide dismutase (SOD)-like activity of OLME (500 μg/mL) were 94.5%, 95.6%, and 63.6%, respectively. OLME and arbutin treatment at 50 μg/mL significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Because arbutin is a well-known tyrosinase inhibitor and was reported as a major constituent of PE in our previous paper [ 10 ], it may be responsible for the inhibitory effects of PE on melanogenesis ( Figure 1 c). However, numerous studies [ 16 , 17 , 18 ] have shown that arbutin did not affect the mRNA expression of MITF; this was consistently found in our observations ( Figure S1 ), which suggested that other components may be involved in the effects of PE. A recent study reported that PCA inhibited melanin production in B16F10 cells, but a mechanism was not determined [ 19 ] and we have previously identified PCA as one of the major constituents of PE [ 10 ].…”
Section: Resultssupporting
confidence: 88%
“…Because arbutin is a well-known tyrosinase inhibitor and was reported as a major constituent of PE in our previous paper [ 10 ], it may be responsible for the inhibitory effects of PE on melanogenesis ( Figure 1 c). However, numerous studies [ 16 , 17 , 18 ] have shown that arbutin did not affect the mRNA expression of MITF; this was consistently found in our observations ( Figure S1 ), which suggested that other components may be involved in the effects of PE. A recent study reported that PCA inhibited melanin production in B16F10 cells, but a mechanism was not determined [ 19 ] and we have previously identified PCA as one of the major constituents of PE [ 10 ].…”
Section: Resultssupporting
confidence: 88%
“…Trying to find natural bleaching agents, Koo et al demonstrated that saponified evening primrose oil can dose-dependently decrease melanin production, in the case of B16 melanoma cells, via a mechanism that involves a reduction in the activity of enzymes, as well as a decrease in mRNA and protein levels of tyrosinase [61]. Additionally, Kim et al showed the significant anti-melanogenic potential of O. laciniata methanol extract on melan-a cells, referring to the same mechanism that suppresses tyrosinase activity, tyrosinase-related proteins (TRP-1 and TRP-2) and microphthalmia-associated transcription factor-M mARN expression [30].…”
Section: Discussionmentioning
confidence: 99%
“…When confluence of 90% was reached, the media was discarded and a scratch was made in the middle of each well, followed by the rinsing of cells with phosphate-buffered saline (PBS). After this step, the cells were treated with different concentrations (10,30, and 60 µg/mL) of the test compound and cell migration was observed by taking pictures at different intervals with an Olympus IX73 inverted microscope documented with a DP74 digital camera (Olympus, Tokyo, Japan). Quantification of A375 cell migration was performed by measuring the cell-free area that resulted after 24 h, using the inverted microscope digital camera software's measurement function, CellSense Dimension 1.17 (Olympus, Tokyo, Japan).…”
Section: Anti-migratory Activity Evaluation Using the Scratch Assay Mmentioning
confidence: 99%
See 2 more Smart Citations